Irrigation infrastructure quality management system toolkit for Sub-Saharan Africa using Ethiopia, Kenya and Uganda as a case study: volume I – guidelines - Amare, Melkamu; Abdella, Y.; Seid, Abdulkarim; Haileslassie, Amare (International Water Management Institute, 2024)
The issue of quality in developing small-scale irrigation projects in Sub-Saharan countries has become a concern. This necessitated the development of a quality management system (QMS) toolkit covering all phases of irrigation project development. The current toolkit was developed to provide guidance and support to establish a robust system that aligns with irrigated agriculture development best practices, standards and regulatory requirements. Literature from the three focal countries – Ethiopia, Kenya and Uganda – was reviewed and stakeholder consultations, field visits and focus group discussions were conducted to learn lessons and gain insight to enrich the proposed parameters and checklists. Based on the lessons learned, the QMS toolkit was created, including a comprehensive set of guidelines, checklists, tools, resources, forms and templates that can help irrigation agencies and stakeholders at all levels implement and maintain an effective quality management system. It is an essential tool for organizations such as irrigation and agriculture ministries, regional bureaus and county offices to assess and improve their performance by meeting quality requirements, standards, regulations and specifications. The toolkit is prepared in two volumes. Volume I covers the reasoning behind the toolkit, its goals and scope, and provides guidelines on how to use the toolkit. It also includes the organization of the toolkit and defines the terminology used. Further, it provides the approach and methods employed and findings obtained during toolkit development.